Environmental Education and Sustainable Development: Assessing Its Impact on Environmental Management Practices - Mwambeo, Humphrey M.; Wambugu, Lydiah N.; Nyonje, Raphael O.; Kariuki, James T. (Journal of Environmental Management and Tourism; Vol 17 No 2 (2026): JEMT, Volume XVII, Issue 2(82), Summer 2026DO - 10.14505/jemt.v17.2(82).01, 2026)
Purpose: This study examined how environmental education influences environmental management practices among households living adjacent Mbololo Forest in Taita-Taveta County, Kenya. It sought to determine whether environmental education improves awareness, encourages positive attitudes toward conservation, and promotes the adoption of sustainable forest management practices. Approach: A quantitative cross-sectional survey was conducted among households residing adjacent Mbololo Forest. The target population consisted of 4,138 households, from whom a sample of 365 respondents were selected using Yamane’s formula. Data were collected using structured questionnaires. A total of 353 completed questionnaires were returned and analyzed, resulting in a response rate of 96.7%. Descriptive statistics and regression analysis were used to examine the relationship between environmental education and environmental management practices. Findings: The results showed that 69.4% of respondents had participated in environmental education programs, which helped increase environmental awareness and improve attitudes toward sustainability. Regression analysis indicated a positive and statistically significant relationship between environmental education and environmental management practices (β = 0.52, p < 0.05). Environmental education explained about 45% of the variation in sustainable practices. Households exposed to environmental education were more likely to practice proper waste management, participate in community conservation activities, and use forest resources more responsibly. Originality/value: The study provides empirical evidence from a rural forest-adjacent community in Kenya, showing that environmental education can play an important role in promoting sustainable environmental management.